2022
DOI: 10.1038/s41563-021-01174-1
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-scale single-crystal monolayer graphene grown on sapphire substrate

Abstract: Currently, the direct synthesis of inch-scale single-crystal graphene on insulating substrates is limited by the lack of metal catalysis, suitable crystallization conditions, and self-limiting growth mechanisms. In this study, we investigated the direct growth of adlayer-free ultra-flat wafer-scale single-crystal monolayer graphene on insulating substrates by the multi-cycle plasma-etching-assisted chemical vapor deposition (MPE-CVD) method. Firstly, an angstrom-scale growth nanochamber was created by fabricat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 44 publications
2
115
0
3
Order By: Relevance
“…In addition, the SAED pattern of CSIG was a set of diffraction rings instead of diffraction spots, which was significantly different from previously reported graphene. 12 , 17 , 54 The ring pattern suggested that the CSIG is made up of random stacking of the graphene layers. Notably, the laser-induced graphene reported by Tour’s group also showed (002) and (100) diffraction rings instead of diffraction spots in an SAED pattern.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SAED pattern of CSIG was a set of diffraction rings instead of diffraction spots, which was significantly different from previously reported graphene. 12 , 17 , 54 The ring pattern suggested that the CSIG is made up of random stacking of the graphene layers. Notably, the laser-induced graphene reported by Tour’s group also showed (002) and (100) diffraction rings instead of diffraction spots in an SAED pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in situ synchrotron techniques with higher spatial, energy, and time resolutions can further improve the sensitivity and the speed of spectral acquisition which will bring unexpected discoveries to understand the facet formation mechanism, the reaction processes in a real circumstance, and the structure-property relationships. (6) Combining in situ characterization with theoretical calculations will provide a new hitting-point to reveal the growth mechanism and activity and selectivity of materials. In addition, theoretical investigations can also be employed to predict new materials with exceptional properties, which can help scientists to design and synthesize target materials.…”
Section: Discussionmentioning
confidence: 99%
“…But it is hard to get the uniform and high‐quality wafer‐scale single crystal due to the introduction of grain boundaries, vacancies, random nucleation in traditional methods. Some efforts have done to grow the wafer‐scale single crystal inorganic 2D, containing graphene, [ 202 ] TMDs, [ 203,204 ] h‐BN, [ 205 ] and Bi 2 O 2 Se. [ 206 ] As for organic materials, a class of ultrathin 2D organic single crystal have been explored in the recent years.…”
Section: Applications and Prospectsmentioning
confidence: 99%